The effect of goalkeeper positioning on goal-side selection between experienced and novice soccer playersperienced players - Wu, Yanjie (Nanyang Technological University, 2022)
Soccer penalties can be a unique scenario for studying human decision-making in a competitive setting. Successful soccer penalties can also determine the outcome of a soccer match (Bar-Eli et al., 2007). PURPOSE: In this study, the effectiveness of goalkeeper positioning is examined to find out if it can influence a penalty taker’s goal side selection during a penalty kick. The following significance is also compared between experienced and novice participants. METHODS: A randomised and controlled experimental design was adopted. 10 experienced soccer players and 10 novice soccer players (age; 23.1 ± 2.5 years) were tasked to kick seven penalty shots against an amateur goalkeeper in the attempt to score. Participants then mentioned their perceived greater goal-side. As a surrogate for the decision-making process and amount of knowledge among shooters regarding penalties, shot direction and perceptual judgment of the displacement were noted. RESULTS: Both novice and experienced groups distributed the ball towards the larger goal side more often in all displacements, with the experienced soccer players doing so more frequently. A disparity between both groups were not seen in the perception task, when the displacement of the goalkeeper was made aware to them. Both the experienced group (26.7%) and the novice group (25%) produced similarly low accuracy in consciously identifying the larger goal-side. CONCLUSION: In brief, goalkeeper displacements of 20 & 30 cm appeared to be the most effective in leading shots towards the larger goal-side. Therefore, goalkeepers may benefit from this strategy the most from standing 20 or 30 cm off-centre during a penalty kick.